Type II diabetes mellitus risk assessment using FINDRISC questionnaire in systemic lupus erythematosus patients - L. V. Kondratieva; T. V. Popkova (Научно-практическая ревматология, 2020)
Objective. To evaluate the prevalence of traditional risk factors in systemic lupus erythematosus (SLE) patients, assess the 10-years risk of developing type 2 diabetes mellitus (DM) in SLE patients and identify those necessitating preventive interventions following altered glucose metabolism using the Finnish Type 2 Diabetes Risk Score (FINDRISK) questionnaire.Materials and methods. The study included 119 SLE patients (107 women, 12 men, with median age 39 [33; 47] years and mean disease duration 6 [1,12] years.The control group included 100 age and sex matched individuals without immune-mediated inflammatory rheumatic diseases and without previous DM history. The 10-years risk of developing type 2 DM in SLE patients and the controls assessed using the Russian adaptation of Finnish Type 2 Diabetes Risk Score questionnaire. Fasting glucose levels in venous blood were measured in all SLE patients. Glucose levels ≥6.1 mmol/L were interpreted as fasting hyperglycemia.Results. The prevalence of traditional type 2 DM risk factors in SLE patients was as follows: abdominal obesity was found in 63.9%, lack of physical activity – in 62.2%, intake of antihypertensive drugs— in 52.9%, BMI ≥25 kg/m2 in 42.0%, unhealthy diets – in 40.3%, family history of DM – in 35.3%, age over 45 years – in 32.8%, history of hyperglycemia episodes – in 15.1%. Abdominal obesity and intake of antihypertensive drugs were more often documented in SLE patients, while all other risk factors were equally represented in SLE and control groups. On average 3 [2; 5] risk factors were found in each SLE patient. Low type 2 DM risk was a more rare phenomenon in SLE patients vs healthy controls (36.1 and 51%, р<0.05). Primary type 2 DM prophylaxis recommended in case of moderate, high and very high risk was more often indicated in SLE vs the healthy controls (29.4 and 17.0%, р=0.03), including those younger than 45 years (18.3 and 6.1% respectively, р=0.05). Fasting hyperglycemia was found in 1.2% patients with low-slightly increased type 2 DM risk and in 16.1% individuals with moderate, high and very high risk (p=0.04).Conclusions. High prevalence of such traditional type 2 DM risk factors as abdominal obesity, lack of physical activity and intake of antihypertensive drugs was demonstrated in SLE patients. Finnish Type 2 Diabetes Risk Score questionnaire identified moderate, high and very high 10-year risk of developing type 2DM in 29.4% SLE patients, necessitating prophylactic interventions in view of altered glucose metabolism.